ANALISIS PEMANFAATAN BENDUNGAN LEUWIKERIS UNTUK KEBUTUHAN IRIGASI DAN KEBUTUHAN AIR BAKU - Sulwan Permana; Ilham Malik (JMTS: Jurnal Mitra Teknik Sipil, 2023)
Leuwikeris Dam was built in the Citanduy Watershed which is a cross-provincial river area (West Java and Central Java Provinces). Utilization of the Leuwikeris Dam as a provider of irrigation water is getting more attention due to the unstable water supply, while farmers need large amounts of water. Another benefit that can be felt by the community is as a source of raw water with a capacity of 845 l/second for Banjar City, Tasikmalaya Regency, and Ciamis Regency. This study aims to determine the discharge required to irrigate an irrigation area of ​​11,216 ha, determine the distribution of raw water and determine the need for raw water for the next 10 years. This research was conducted by taking secondary data which was then calculated. The results of the calculation show that the highest discharge to irrigate an irrigation area of ​​11,216 ha is in April of 18,083.72 lt/sec. The distribution of raw water discharge from the availability of 845 lt/sec for each region, namely: Banjar City at 24.07 lt/sec, Tasikmalaya Regency at 142.16 lt/sec, and Ciamis Regency at 679.08 lt/sec. The need for raw water discharge for the next 10 years is 884 lt/sec. Keywords: Raw Water, Dam, Discharge, Irrigation, Dam Benefits